Koagulyant-adsorbenttiń adsorbciyalıq qásiyetin kolorimetriyalıq usıl menen úyreniw (SCIENCE and SOCIETY, 2025)
This article presents the adsorption properties of thermally activated coagulants-adsorbents, the structural- sorption indicators of coagulants-adsorbents, and the pore volume, as well as their dependence on adsorption.